Autophagy as a potential therapeutic target in regulating improper cellular proliferation - Kumar, Prashant; Choudhary, Akash; Kinger, Sumit; Jagtap, Yuvraj Anandrao; Prajapati, Vijay Kumar; Chitkara, Deepak; Chinnathambi, Subashchandrabose; Verma, Rahul Kumar; Mishra, Amit (Frontiers in Pharmacology, 2025)
Autophagy is a degradative process that makes rapid turnover of old and impaired proteins and organelles possible. It is highly instigated by stress signals, like starvation, and contributes to the cell’s homeostasis. Autophagy performs a crucial function in keeping cell genomic integrity stable. Impaired autophagic flux is implicated in neurodegenerative diseases, abnormal ageing, and cancerous diseases. In diseases like cancer, autophagy performs a dualistic function; it can have both a tumor-suppressive and supportive role. Autophagy in the initial phases of tumorigenesis maintains the integrity of the genome and, if it fails, leads to cell death, thus having a tumor-suppressive role. Meanwhile, autophagy also imparts the function of the pro-survival mechanism in the latter stages of tumorigenesis and supports the cancerous cells in surviving conditions like hypoxia and increased oxidative stress. Autophagy also helps cancerous cells develop drug resistance in some cases. Thus, modulation of the autophagic mechanism is a possible therapeutic strategy in cancer therapy as its inhibition can sensitise cancer cells to anti-cancerous drugs. The promotion of autophagy, in some cases, can also safeguard cells from toxic protein aggregation and enhanced oxidative stress. Excessive autophagy can result in autophagic cell death. Autophagy also regulates several cellular processes and cell death pathways, like apoptosis. Therefore, an in-depth knowledge of the autophagy process and its regulating molecules is critically important. Pharmaceutical small molecules or cellular target modulation can help modulate the cellular autophagy process in the context of specific disease conditions.